Lean customer development : build products your customers will buy - Alvarez, Cindy (Lean series., 2021)
How do you develop products that people will actually use and buy? This practical guide shows you how to validate product and company ideas through customer development research-before you waste months and millions on a product or service that no one needs or wants. With a combination of open-ended interviewing and fast and flexible research techniques, you'll learn how your prospective customers behave, the problems they need to solve, and what frustrates and delights them. These insights may shake your assumptions, but they'll help you reach the "ah-ha!" moments that inspire truly great products. Validate or invalidate your hypothesis by talking to the right people Learn how to conduct successful customer interviews play-by-play Detect a customer's behaviors, pain points, and constraints Turn interview insights into Minimum Viable Products to validate what customers will use and buy Adapt customer development strategies for large companies, conservative industries, and existing products